"Girls Are Like Flowers; Boys Are Like footballs": How Fathers Hope to Configure Their Sons' Masculinity. Issue 1 (1st June 2021) - Herrera, Florencia
Abstract: To contribute to the discussion about how masculinity—understood as a configuration of gender practices (Connell 2000)—is reproduced, this paper analyzes fathers' discourse about the gender of their sons and daughters. I carried out a qualitative longitudinal study in Chile during which 28 first-time fathers were interviewed before and after their child's birth or arrival (adoption). I suggest that these fathers see gender in essentialist, dichotomous, and hierarchical terms. They expect to shape their sons' gender practices according to hegemonic masculinity (discouraging gender practices associated with femininity or homosexuality). In the study, no attempt to reformulate masculine gender practices was observed but, rather, an interest on the fathers' part in maintaining the patriarchal gender order.